To simplify the expression \(\sqrt{32x^6}\), we can break it down as follows:
-
Factor out the components inside the square root:
\[ \sqrt{32x^6} = \sqrt{32} \cdot \sqrt{x^6} \]
-
Simplify \(\sqrt{32}\):
The number \(32\) can be factored as \(16 \times 2\): \[ \sqrt{32} = \sqrt{16 \cdot 2} = \sqrt{16} \cdot \sqrt{2} = 4\sqrt{2} \]
-
Simplify \(\sqrt{x^6}\):
Using the property that \(\sqrt{x^n} = x^{n/2}\): \[ \sqrt{x^6} = x^{6/2} = x^3 \]
-
Combine the simplified terms:
Now we can put it all together: \[ \sqrt{32x^6} = 4\sqrt{2} \cdot x^3 = 4x^3\sqrt{2} \]
Thus, the expression equivalent to \(\sqrt{32x^6}\) is:
\[ \boxed{4x^3\sqrt{2}} \quad \text{(Option A)} \]